Engaging Citizens in the Decision-Making Process - Lielpēters, Eduars (Klaipeda University, 2019)
The rapid development of internet and technologies in the 21th century is providing an opportunity for the development of digital democracy – citizen engagement in the decision-making process in an easier, faster and more contemporary way. The paper analysis Latvian public administration’s attitude to the development of digital democracy in Latvia, looking into digital engagement as a possible solution that could foster the low rates of civic and political participation in Latvia. Research methods of the paper consists of an analysis of academic publications on digital democracy and political engagement, and survey to the representatives of the public administration in Latvia. Conclusions of the paper suggest that there are good preconditions for the development of digital democracy in Latvia, however, there is a need for a common regulation for how digital communication and online participation is coordinated. Public institutions should pay more attention to Latvian youth, educating them about public administration and political engagement, thus ensuring that gradually Latvian citizens become more knowledgeable about advantages and necessity to participate in the decision-making process of public administration in Latvia.
Keywords: citizen engagement; digital democracy; public institutions; social media; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Public sector research